POTENTIAL AREA ANALYSIS IN THE AGROPOLITAN DEVELOPMENT AREA IN BOJONEGORO REGENCY, EAST JAVA PROVINCE, INDONESIA - Via Hamida Dwita Noer Azizia; Syamsul Huda (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
The purpose of this study is to analyze the potential of the region in developing an agropolitan area in Bojonegoro Regency, East Java Province through the location quotient, shift share. Data collection techniques generally used primary and secondary survey methods. The results show that based on the results of the Location Quotient (LQ) calculation in Bojonegoro sub-district which are included in the base sector, namely the mining sector, government administration sector, information and communication sector and the mining sector. is; agriculture sector, mining and quarrying sector, manufacturing industry sector, electricity and gas procurement sector, wholesale and retail trade sector, transportation and warehousing sector, accommodation and food and beverage provider sector, information and communication sector, financial and insurance services sector, real estate sector , the corporate service sector and the government administration sector